Analysis Of Information System For Scientific Work Title Submission Selection At Digitech University - Merliana, Elsa (Media Jurnal Informatika, 2025)
This study aims to analyze the information system for scientific worktitle submission selection in the D3 Management Informatics Study Program at Digitech University. Based on observations, the title submission process is still carried out conventionally using Google Form and Microsoft Excel, which causes several problems such as title duplication, verification delays, and data tracking difficulties. This study uses observation, interview, and library research methods. SWOT analysis is conducted to identify strengths, weaknesses, opportunities, and threats of the current system. The results show that the conventional system is less efficient and needs to be immediately replaced by an integrated digital system that can improve the effectiveness of academic processes. The system recommendations provided are expected to support the institution's vision as a digital technology-based campus.